Scaling up of hydrogen supply chains: The role of supply chain governance - Jakob Keller; Florian Biniosek; Rainer Lasch (Logistics Research, 2023)
The purpose of this study is to explore if and how interfirm governance can foster the scaling up of hydrogen supply chains. We applied an interview study approach conducting semi-structured interviews with 13 experts from hydrogen production, storage, transportation, and utilization. This research shows that the industry background and the engagement intentions of actors, as well as political funding programs, strongly influence the choice of governance mechanisms to coordinate the scaling up of hydrogen supply chains. While formal governance mechanisms are mainly used for economic safeguarding, informal mechanisms enable the tremendous level of collective learning necessary for the scaling up of hydrogen supply chains. Novel theoretical and managerial insights are provided regarding the influence of governance mechanisms on the scaling up process and showing the importance of collective learning when building hydrogen supply chains.
Keywords: 650; Scaling Up; Hydrogen; Supply chain; Governance; Mechanism; Collective Learning